Sinergi Akuntan Milenial dan Petani Milenial di Era Ekonomi Digital - Surepno Surepno; Chairul Anam (Universitas Pahlawan Tuanku Tambusai, 2022)
The university has a role in community service through providing empowerment assistance, training, counseling, mentoring, mentoring and to realize their potential, as well as helping to improve the quality of life and development. Based on the problems faced in the current digital era, in the context of the community service program, we have held a webinar with the theme of the synergy of millennial accountants and millennial farmers in the digital era. The method of implementing Service Activities is to use virtual meeting media by educating young accountants and practitioners in the agricultural sector. In this activity, it can be concluded that the existence of village funds distributed to the community creates an opportunity for young accountants to synergize with farmers in increasing economic value by providing education about the importance of capital management in accordance with the principles in accounting. The activity went well and smoothly, although there were also a few obstacles because there were several unsupportive factors such as the limited frequency of the internet signal, but overall the service ran smoothly.